ANALYSIS OF THE ESTABLISHMENT OF STUDENT DISCIPLINE CHARACTER IN ONLINE AND OFFLINE LEARNING IN CLASS II SD PLUS SUNAN AMPEL, KEDIRI CITY - Fanani, Moh. Zainal; Rahmawati, Novi Rosita; Khotimah, Husnul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
In learning the character of discipline as one of the characters in Core Competence (KI)-2, social attitudes show honest, disciplined, polite, confident, caring, and responsible behavior in interacting with family, friends, teachers, neighbors, and the country. Based on this, the classroom teacher becomes the main actor in shaping the disciplined character of students in online and offline learning. This research method is qualitative with the type of case study, data collection techniques using observation, interviews, and documentation. The results showed that the formation of student discipline character in online and offline learning in class II SD Pls Sunan Ampel City Kediri includes example giving gifts, giving sanctions, connecting books, and habituation. Contraints and solutions for the formation of disciplinary character in online and offline learning include the limitations of class II teachers in appling the method of formation and there are different student characters. The solution given is to give reprimand, advice, motivation, and cofirm collaboration with parents. Keywords : Discipline Character, Online and Offline Learning.